Uma didática da invenção: re-envisioning the material world in the poetry of Manoel de Barros. - Smith, David Peter Woodhead (2016)
The poetry of Manoel de Barros has often been characterized as part of a regional canon. This characterization belies its importance not only within the confines of the Brazilian canon, but as a contribution to C20 literature in general. Barros's poetry explores themes which are crucially important to navigating our existence in the modern world, and this thesis focuses on his engagement with the natural and material world. Drawing on theories from post-modern critical thinking and eco-criticism, I demonstrate how Barros's poetry can not only be read in the light of these critical idioms, but frequently expands upon or confounds them, revealing poetry as a form of modern critique - and indeed perhaps the most pertinent and incisive form of critique available to us when dealing with questions of materiality, reality and the natural world.